Prevalence and risk factors of diarrhea morbidity among under-five children in India: A systematic review and meta-analysis - Ganguly, Enakshi; Sharma, Pawan K; Bunker, Clareann H (Indian Journal of Child Health, 2015)
Background: Acute diarrhea accounts for a huge burden of infectious diseases in under-five children. Objective: This systematic review was carried out to study the prevalence and associated risk factors of diarrhea among Indian children aged <5 years. Methods: Papers were identified by a comprehensive electronic search of relevant medical subject heading (MeSH) terms in PubMed. Identified articles were independently reviewed against inclusion/exclusion criteria and rated for quality. 15 articles were abstracted and reviewed to identify the reported prevalence and risk factors for childhood diarrhea. Meta-analysis was done for calculating the pooled prevalence of diarrhea and point estimates of risk factors using random effects model with use of appropriate population weights, and depicted using forest plot. Results: The overall prevalence of diarrhea between 2002 and 2013 was 21.70% (95% confidence interval [CI]: 11.24-34.46). The significantly associated risk factors were malnutrition (odds ratio [OR]: 1.73, 95% CI: 1.53-1.96) and anemia (OR: 1.71, 95% CI: 1.29-2.28) in child, and low socioeconomic status (OR: 7.14, 95% CI: 2.19- 23.32). Age of the child <24 months, not breastfeeding, mothers’ low literacy status and untreated drinking water did not show a significant association. Sex of the child, religion, higher education of mothers, and seasonality were found to be inconsistently associated in single studies. Conclusion: It was concluded that there is sufficient evidence on the association of childhood diarrhea with socio-demographic factors, but evidence on other contributory factors including breastfeeding and vaccination is inconclusive. There is need to conduct more analytical studies on lesser known risk factors of diarrhea to establish their risk factors in Indian children.